Effect Of Empagliflozin On Heart Failure Outcomes In Post-Acute Myocardial Infarction Patients (Journal of Pharmaceutical Negative Results, 2021)
Background: Acute myocardial infarction (AMI) is a leading cause of morbidity and mortality worldwide, often resulting in heart failure (HF) as a significant complication. Recent studies have highlighted the potential benefits of sodium-glucose cotransporter-2 (SGLT2) inhibitors, particularly empagliflozin, in improving cardiovascular outcomes in patients with heart failure.Objectives: To evaluate effects of empagliflozin in post-AMIpatients in term of hospitalization rates, improvement in left ventricular functionand cardiovascularmortality.Study Design: A randomized, placebo-controlled trialPlace and Duration of the Study: Department of Cardiology, MTI Gajju Khan Medical College, Swabi, KP, DHQ teaching hospital Swabi, Pak Medical Center and Hospital Peshawar and DHQ teaching hospital Bannu from January 2020 to April 2021 for a total duration of 16 months.Methodology: Six hundreds 600 Patients hospitalized for AMI and at risk for heart failure were enrolled and assigned to receive either empagliflozin (10 mg daily) or placebo within 14 days of admission. Demographic data, base line characteristics of patients and LVEFwas recorded at baseline. Patients in both groups were followed every month as their follow up for a total duration of 6 months. Three parameters were recorded at the end of study including frequency of heart failure hospitalization, improvement in ejection fraction and mortality due to cardiovascular cause in both groups. These parameters were compared using statistical tools to find the difference in both groups.Results: The group that received empagliflozin (n = 300) had a lower number of heart failure hospitalizations, at 54 (18%) against 90 (30%) in the placebo group (n = 300), giving 12% absolute risk reduction. LVEF increased by 10 ± 3% in the empagliflozin group compared with 4 ± 2% in the placebo group. Mortality rate was also reduced with 24 patients (8%) in the empagliflozin group as distinguished from 45 patients (15%) in the placebo group. Conclusion: Empagliflozin has decreased HF hospitalization rate, improved left ventricular function and reduced mortality in patients after AMI.